Authority of The Indonesian Corruption Eradication Commission Post Amendment to Law No. 19 of 2019: Regresive or Progressive in Law Enforcement? - Fransiscus Xaverius Hastowo Broto Laksito; Rian Saputra; Doris Rahmat; Waluyo Slamet Pradoto; Aji Bawono; Kesya Zhalibina Sunarto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The aim of this research is to look at the transformation of the Corruption Eradication Commission Institution after the revision of the new Indonesian Corruption Eradication Commission (KPK) Law in supporting corruption prevention policies in Indonesia. This research was conducted using doctrinal legal research methods or normative legal research. In this research, the approaches used include: Statute Approach. Conceptual Approach, Historical Approach, Case Approach. The research results show that: 1) The authority of the Corruption Eradication Commission (KPK) after the promulgation of Law no. 19 of 2019 concerning the Second Amendment to Law no. 30 of 2002 concerning the Corruption Eradication Commission, with the addition of the Supervisory Board within the Corruption Eradication Commission (KPK)  Institution which has quite large authority, namely not only supervision but also the implementation of the authority of the Corruption Eradication Committee, namely that it must first obtain permission from the Supervisory Board before carrying out wiretapping, searches and/ or the confiscation is carried out by the Corruption Eradication Commission, this can hinder law enforcement in eradicating criminal acts of corruption and can also affect the independence of the Eradication of Corruption Crimes within the Corruption Eradication Commission Institution.